Clickwrap Agreements in Indonesian FinTech Services: Legal Validity, Doctrinal Tensions, and the Limits of Enforceability under Civil Law - Suriati; Syaddan Dintara Lubis (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
The rapid expansion of financial technology (FinTech) in Indonesia has transformed contractual relations through standardized electronic contracts, particularly clickwrap agreements in which consent is expressed by affirmative digital action. This article examines the legal construction and enforceability of clickwrap agreements under Law No. 1 of 2024 on Electronic Information and Transactions and evaluates their validity from the perspective of Indonesian civil contract law, with reference to Article 1320 of the Civil Code. Using a doctrinal legal analysis that integrates statutory interpretation and conceptual assessment of contractual consent, the study interrogates the coherence between procedural digital validity and substantive agreement requirements. The findings reveal that although clickwrap agreements are formally recognized as binding electronic contracts, a normative tension persists between technological formalism and the civil law conception of consent as a free and informed manifestation of will. Standardized contractual architectures and information asymmetry may weaken substantive autonomy despite formal compliance. The article argues for a recalibrated enforceability framework that incorporates autonomy, transparency, and contractual fairness to support regulatory harmonization and sustainable FinTech governance.